A variant of RSA using continued fractions. (2nd January 2022) - Athukorala, Pabasara; Chathurangi, Madusha; Ranasinghe, Rajitha
Abstract: In the modern world, the need for secure communication is of utmost importance and in that cryptography plays a significant role. The RSA algorithm is one of the most widely used public key cryptosystems and mathematicians throughout the world are proposing new variants for RSA in order to overcome its drawbacks. In our system, we introduce a new variant for the textbook RSA algorithm using continued fractions. We have developed the key generation using continued fractions and further improved the encryption using a technique similar to that of padding. We have also proved that our system is secure against the meet-in-the-middle-attack in contrast to the textbook RSA algorithm.